The Origins of the Division of Labor in Pre-Modern Times - Emilio Depetris-Chauvin; Ömer Özak (Institute of Labor Economics (IZA), 2018)
This research explores the historical roots of the division of labor in pre-modern societies. It advances the hypothesis and establishes empirically that intra-ethnic diversity had a positive effect on the division of labor across ethnicities in the pre-modern era. Exploiting a variety of identification strategies and a novel ethnic level dataset combining geocoded ethnographic, linguistic and genetic data, it establishes that higher levels of intra-ethnic diversity were conducive to economic specialization in the pre-modern era. The findings are robust to a host of geographical, institutional, cultural and historical confounders, and suggest that variation in intra-ethnic diversity is the main predictor of the division of labor in pre-modern times.
Keywords: D74; F10; F14; J24; N10; O10; O11; O12; O40; O43; O44; Z10; Z13; 330; comparative development; division of labor; economic specialization; intra-ethnic diversity; cultural diversity; population diversity; genetic diversity; linguistic diversity